2017
DOI: 10.1530/endoabs.49.ep753
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol increases hepatic SHBG expression through human constitutive androstane receptor: a new Contribution to the French Paradox

Abstract: Sex hormone-binding globulin (SHBG) carries sex steroids in blood regulating their bioavailability. Red wine consumption increases plasma SHBG levels, and we have discovered that resveratrol, a polyphenol enriched in red wine, acts specifically through the human constitutive androstane receptor (CAR), a drug/xenobiotic detoxification gene regulator, to increase hepatic SHBG production. Chromatin immunoprecipitation and luciferase reporter gene assays show that human CAR binds to a typical direct repeat 1 nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 60 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Why the red wine high in resveratrol only increased plasma SHBG levels in women is intriguing and it merits further investigation in a different setting of experiments. We have previously reported using HepG2 cells and the humanized SHBG‐CAR transgenic mice [ 21 ] that resveratrol increases plasma SHBG levels through the constitutive androstane receptor (CAR). In this regard, a possible explanation for the sexual dimorphic response to resveratrol found in our pilot study could be influenced by the differences in expression of CAR between men and women and the different modulating action of sex steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why the red wine high in resveratrol only increased plasma SHBG levels in women is intriguing and it merits further investigation in a different setting of experiments. We have previously reported using HepG2 cells and the humanized SHBG‐CAR transgenic mice [ 21 ] that resveratrol increases plasma SHBG levels through the constitutive androstane receptor (CAR). In this regard, a possible explanation for the sexual dimorphic response to resveratrol found in our pilot study could be influenced by the differences in expression of CAR between men and women and the different modulating action of sex steroids.…”
Section: Discussionmentioning
confidence: 99%
“…These studies allowed us to show that resveratrol increased hepatic SHBG production through the constitutive androstane receptor (CAR). [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[45,[47][48][49][50][51][52] In a series of comprehensive experiments, we have shown that red wine and resveratrol increase SHBG production in HepG2 cells. [3] Mechanistically, resveratrol acts specifically through the human constitutive androstane receptor (CAR), a drug/xenobiotic detoxification gene regulator, [53][54][55][56] to increase hepatic SHBG production by binding to a DR-1 element, present in the footprint 3 region of the SHBG promoter. [3] These results were corroborated in vivo using a humanized SHBG/CAR transgenic mouse, where plasma SHBG levels were increased by resveratrol consumption.…”
Section: Red Wine (Resveratrol)mentioning
confidence: 99%
“…[3] Mechanistically, resveratrol acts specifically through the human constitutive androstane receptor (CAR), a drug/xenobiotic detoxification gene regulator, [53][54][55][56] to increase hepatic SHBG production by binding to a DR-1 element, present in the footprint 3 region of the SHBG promoter. [3] These results were corroborated in vivo using a humanized SHBG/CAR transgenic mouse, where plasma SHBG levels were increased by resveratrol consumption. [3] Moreover, SHBG expression correlated significantly with CAR mRNA levels in human liver biopsies.…”
Section: Red Wine (Resveratrol)mentioning
confidence: 99%
See 1 more Smart Citation